Crater Retention Timescales of Brain Coral Terrain Record Past Climatic Change on Mars - Alexander M. Morgan; Eldar Z. Noe Dobrea; Kyle A. Pearson; Alphan Altinok (The Planetary Science Journal)
Glacial landforms on Mars offer an opportunity to decipher the planet’s recent climate history. We used crater size frequency distributions of brain coral terrain on concentric crater fill, lobate debris aprons, and lineated valley fill, all of which have been previously interpreted to be glacial landforms, to make inferences about the evolution of these surfaces. We mapped brain coral terrain in Ismenius Lacus, Utopia Planitia, and Arcadia Planitia, and classified superposing impact craters by degradation state in order to derive detailed degradation histories across a broad area of the northern martian midlatitudes. Our data support a period of glacial landform deflation of ∼10 m beginning at some point after ∼25 Ma and ceasing at ∼3 Ma. The timing of the cessation of this deflationary period closely corresponds to a modeled shift in Mars' mean obliquity from mean 35° to mean 25°. Our results thus offer an important midlatitude geologic record of Mars’ late-stage obliquity and climatic evolution during the Late Amazonian.